الجباية البيئية آلية لضمان حماية البيئة - عماري, سناء (University of eloued - جامعة الوادي, 2018)
يعد من ضمن الأولويات والتحديات التي تولي الدولة اهتماماتها البالغة، إيجاد الآليات والأدوات الاقتصادية للحد من أثار نشاطاتها و التوسع على حساب البعد البيئي التلوث البيئي حيث تعد الجباية البيئية أداة اقتصادية مالية لإدارة الموارد البيئية و آلية ردعية وقائية لتغيير السلوكيات البيئية للمؤسسات ، وضمانة لحماية البيئة من خطر التلوث والتجاوزات التي تفضي إلى استنزاف الثروة، وعدم مراعاة مصلحة الأجيال المستقبلة. بدمج البعد البيئي في النظام الإنتاجي في المؤسسات الاقتصادية، للحد من ظهور المشكلات البيئية الناتجة عن الجشع في استغلال الموارد الطبيعية والتلوث البيئي الناتج عن مختلف الأنشطة الاقتصادية It is one of the priorities and challenges that the State attaches its utmost importance to the establishment of economic mechanisms and tools to reduce the effects of its activities and to expand at the expense of environmental dimension environmental pollution, where environmental taxation is a financial economic tool for the management of environmental resources, a preventive deterrent mechanism to change the environmental behavior of enterprises, Of the risk of pollution and abuses leading to depletion of wealth, and not taking into account the interest of future generations. By integrating the environmental dimension into the productive system of economic institutions, to reduce the emergence of environmental problems resulting from greed in the exploitation of natural resources, and environmental pollution resulting from various economic activities
مقال
Keywords: حماية البيئة ، النظام الجبائي الردعي ، النظام الجبائي التحفيزي Environmental protection, repressive tax system, tax incentive system